Synthesis, Molecular Modeling, and Evaluation of Novel Sulfonylhydrazones as Acetylcholinesterase Inhibitors for Alzheimer's Disease. Issue 11 (22nd September 2017) - Fernandes, Thais B.; Cunha, Micael R.; Sakata, Renata P.; Candido, Thalita M.; Baby, André R.; Tavares, Maurício T.; Barbosa, Euzébio G.; Almeida, Wanda P.; Parise‐Filho, Roberto
Abstract : Alzheimer's disease (AD) is the most common type of dementia and related to the degeneration of hippocampal cholinergic neurons, which dramatically affects cognitive ability. Acetylcholinesterase (AChE) inhibitors are employed as drugs for AD therapy. Three series of sulfonylhydrazone compounds were designed, and their ability to inhibit AChE was evaluated. Fifteen compounds were synthesized and twelve of them had IC50 values of 0.64–51.09 μM. The preliminary structure–activity relationships indicated that the methylcatechol moiety and arylsulfonyl substituents generated better compounds than both the benzodioxole and alkylsulfonyl chains. Molecular dynamics studies of compound6d showed that the interaction with the peripheral binding site of AChE was similar to donepezil, which may explain its low IC50 (0.64 μM). Furthermore, the drug‐likeness of6d suggests that the compound may have appropriate oral absorption and brain penetration. Compound6d also presented antiradical activity and was not cytotoxic to LL24 cells, suggesting that this compound might be considered safe. Our findings indicate that arylsulfonylhydrazones may be a promising scaffold for the design of new drug candidates for the treatment of AD. Abstract : The newly designed sulfonylhydrazones inhibited acetylcholinesterase (AChE) with IC50 values between 0.64 and 51.09 μM. The most active compound, (E)‐ N ′‐(4‐hydroxy‐3‐methoxybenzylidene)‐4‐methoxybenzenesulfonohydrazide (6d ), is not cytotoxic to LL24 cells and, due to its drug‐likeness, appears suitable for oral absorption and brain penetration.